Childhood predictors of adult intimate partner violence perpetration and victimization - Curtis, Ashlee (Journal of family violence, 2023)
Purpose: This systematic review is a 5-year update of a previously conducted review on the longitudinal predictors of domestic violence perpetration and victimization. This review adopted the term ‘Intimate Partner Violence (IPV)’ to align with current literature and addressed two aims: to identify any novel longitudinal risk factors since the previous review, and to determine if a distinction could be drawn between risk factors for perpetration and victimization (a limitation identified by the previous review). Methods: Twelve studies met the inclusion criteria of prospectively investigating childhood/adolescent predictors (prior to age 18) for adulthood IPV perpetration and victimization. Peer-reviewed papers were identified via the following databases in November 2020: MEDLINE, APA PsycINFO, SocINDEX, EMBASE, and Scopus. Study quality was assessed using the Cambridge Quality Checklists. Results: Consistent with the previous review, child and adolescent abuse, family of origin risks, child and adolescent behavioral problems, and adolescent peer risks were identified as significant predictors of IPV perpetration and victimization. The current review, however, adds nuance to these findings, identifying potential moderating and/or mediating factors and additional risk factors, including mental health and cultural and attitudinal risks. Conclusion: This review re-emphasizes the importance of developmental risk factors for adulthood IPV perpetration and victimization, and their role in prevention and intervention efforts.